2006
DOI: 10.1016/j.jinorgbio.2006.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Decavanadate interactions with actin: Inhibition of G-actin polymerization and stabilization of decameric vanadate

Abstract: Decameric vanadate species (V10) inhibit the rate and the extent of G-actin polymerization with an IC50 of 68 ± 22 lM and 17 ± 2 lM, respectively, whilst they induce F-actin depolymerization at a lower extent. On contrary, no effect on actin polymerization and depolymerization was detected for 2 mM concentration of ''metavanadate'' solution that contains ortho and metavanadate species, as observed by combining kinetic with 51 V NMR spectroscopy studies. Although at 25°C, decameric vanadate (10 lM) is unstable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
102
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(112 citation statements)
references
References 38 publications
10
102
0
Order By: Relevance
“…3A), as described recently [22]. In fact, the concentrations of each vanadate oligomer calculated by integration of the respective areas of the NMR spectra, as a function of total vanadate, exhibit different profiles according to the species.…”
Section: Characterization Of Vanadate Solutionsmentioning
confidence: 87%
See 2 more Smart Citations
“…3A), as described recently [22]. In fact, the concentrations of each vanadate oligomer calculated by integration of the respective areas of the NMR spectra, as a function of total vanadate, exhibit different profiles according to the species.…”
Section: Characterization Of Vanadate Solutionsmentioning
confidence: 87%
“…It has been suggested that V10 decomposition is slow enough to allow studying its effects in biochemical systems [16,17], not only in vitro but also in vivo [16][17][18][19][20][21]. More recently, it was described that V10 can be stabilized upon interaction with cytoskeleton and membrane proteins [22]. Therefore, we cannot exclude the hypothesis that V10 may also occur at physiological conditions for long enough to induce different biological effects in comparison to metavanadate.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…[4][5][6] In addition, V 10 sition may be prevented through binding to specific proteins, which apparently retard dissociation. Increases in the half-life from 5 to 17 hours in the presence of sarcoplasmic reticulum vesicles, and to 27 hours in the presence of actin were found at room temperature and pH 7.0, 25 whereas no effects were observed with myosin, even though it is known to have a highaffinity V 10 -binding site. 26 Decavanadate was observed to induce protein cysteine oxidation and vanadyl formation in the presence of SR Ca 2+ -ATPase and actin, whereas no effects were observed on incubation with monomeric vanadate.…”
Section: Introductionmentioning
confidence: 88%
“…In previous studies [2][3][4][5][6][7][8], we have demonstrated that once formed in aqueous solutions decameric vanadate decomposition is slow enough to allow studying differential effects between decameric and monomeric vanadate not only in vitro but also in vivo. Furthermore, decameric vanadate is stabilized upon interaction with cytoskeleton and membrane proteins, while it affects calcium translocation by the sarcoplasmic reticulum calcium pump and it prevents actin polymerization [9].…”
Section: Introductionmentioning
confidence: 99%